2018
DOI: 10.21873/anticanres.12420
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Trimodal Therapy in Elderly Patients with Esophageal Cancer: Prognostic Value of the Charlson Comorbidity Index

Abstract: Routine use of the CCI may help in the pretreatment risk stratification of elderly patients with esophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The propensity to prescribe multimodal treatment was increased in patients aged<70 years in good general condition (low ASA score) with advanced cancer (cT3-4/cN+). Accordingly, Charlson's comorbidity index ( [18]) was the most important predictor of tolerance to nCRT in an Italian series aged >65 years with esophageal squamous cell carcinoma and adenocarcinoma [19]. Interestingly, the proportion of patients receiving standard multimodal care (perioperative/adjuvant treatment and surgery) was relatively low in Canadian series aged 75 years or older, affected by either gastric or esophageal carcinoma (14%) [20] or localized gastric or gastroesophageal junction cancer (13%) [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The propensity to prescribe multimodal treatment was increased in patients aged<70 years in good general condition (low ASA score) with advanced cancer (cT3-4/cN+). Accordingly, Charlson's comorbidity index ( [18]) was the most important predictor of tolerance to nCRT in an Italian series aged >65 years with esophageal squamous cell carcinoma and adenocarcinoma [19]. Interestingly, the proportion of patients receiving standard multimodal care (perioperative/adjuvant treatment and surgery) was relatively low in Canadian series aged 75 years or older, affected by either gastric or esophageal carcinoma (14%) [20] or localized gastric or gastroesophageal junction cancer (13%) [21].…”
Section: Discussionmentioning
confidence: 99%
“…The propensity to prescribe multimodal treatment was increased in patients aged<70 years in good general condition (low ASA score) with advanced cancer (cT3-4/cN+). Accordingly, Charlson’s comorbidity index ([18]) was the most important predictor of tolerance to nCRT in an Italian series aged >65 years with esophageal squamous cell carcinoma and adenocarcinoma [19].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the adjuvant treatments, this association is not surprising since the efficacy of adjuvant treatments to prevent recurrence and metastasis, and improve survival is the reason for giving adjuvant therapy in the first place[ 3 - 5 , 15 , 16 , 21 ]. Regarding the CCI, Bernardi et al [ 22 ] showed that patients with esophageal cancer who completed their treatment plan had a lower CCI than those who eventually dropped out, affecting the prognosis. Yamashita et al [ 23 ] and Aoyama et al [ 24 ] showed that the CCI was correlated with the prognosis of patients who undergo curative resection of esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%